The Influence of Learning Motivation on Learning Chinese As a Foreign Language - Liu, Suhan (Transactions on Social Science, Education and Humanities Research, 2024)
This paper aims to systematically review the benefits of constructivism theory combined with intrinsic learning motivation in Chinese as a foreign language classroom. By combing the relevant literature, the author can find the dominant position of constructivism theory in the Chinese classroom, which leads to the importance of intrinsic learning motivation. This theory emphasizes students' initiative, situationality and sociality, and provides a convenient way for cross-cultural learning. In the Chinese as a foreign language classroom, educators understand and analyze the learners according to the national conditions, integrate constructivism into the classroom, and explore a series of teaching models and methods that meet the reality of foreign learners. However, in the real classroom teaching process, there are also many problems, such as the cultural differences between teachers and students, students' learning objectives and so on. In the future, the researchers should continue to deepen the research on the influence of intrinsic learning motivation on Chinese acquisition under the guidance of constructivism theory, improve relevant teaching models, and better promote the innovation and development of international Chinese education. The research of this paper is of great significance to the application of constructivism theory in the field of international Chinese education under the role of intrinsic motivation, and to the prospect of constructivism theory for the future development of Chinese learning.